Critical Success Factors of Business Intelligence System in Organizations - Mashayekh, Talha AbedelFattah; Al-Aidaros, Hashem Mohammed; Khoj, Haitham Zaker (Journal of Economic, Administrative and Legal Sciences, 2023)
Business intelligence has accumulated much attention in the last decades, and organizations have invested much money in its operation to make better decisions and achieve a great future. The business intelligence system has made it feasible for more effortless data adaptation. Investigations improve an organization's performance when it arrives at a more valuable insight and improves decision-making. This report presents a systematic literature review on business intelligence and which critical success factors improve the efficiency of the BIS. CSFs for successful BI implementation were examined vastly earlier. The immediate objective of this research is to prioritize the CSF articles for BI implementation success. Using the systematic literature review as the methodology of this report we have investigated the findings of 6 studies and a crucial examination of the specified papers. We discovered that these studies are investigating 344 sub-studies. These 344 sub-studies were carrying into consideration 115 CSF. These factors were shown 796 times in these sub-studies. After analyzing the 115 CSF, we came to the essential CSF, 17 factors, whose weight is 15% of the total factors. The 17 factors were shown 589 times in the sub-studies. The importance of the 17 factors is around 80% of the total 115 factors. The findings of this report motivate BI stakeholders in organizations to concentrate their actions and restricted resources on these 17 essential CSF areas to gain the most significant advantages from the BI system itself.
Keywords: Business intelligence system BIS; BI success; Critical success factors CSFs; Information system success; BI implementation